Proteomic Characterization of Oestrus ovis Larvae by SDS Page Analysis - Kiran, A. Vamshi; Murthy, G. S. Sreenivasa; Kumar, M. Udaya; Kalyani, P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study focuses on the proteomic characterization of crude somatic pooled L2 and L3 antigens from Oestrus ovis larvae. The larvae were homogenized in a buffer containing 20 mM Tris-HCl, 50 mM NaCl, 1 mM EDTA, 1 mM PMSF, and 6 mM urea, followed by centrifugation at 4 ºC to obtain soluble crude larval proteins. The protein concentration of the pooled crude somatic L2 and L3 antigen was determined to be 27.4 mg/ml using the Lowry method. From 26 second-stage and 13 third-stage larvae, 12 ml of antigen was obtained, aliquoted, and stored at -70 ºC. For protein profile analysis, SDS-PAGE was performed with varying concentrations of CSL proteins, revealing multiple polypeptides. Specifically, 50 µg of CSL protein loaded on SDS-PAGE resolved into 27 distinct polypeptides with molecular weights ranging from 14.27 kDa to 81.64 kDa. This diversity in molecular sizes underscores the complex nature of the CSL protein, indicating the presence of various protein components within the larval stages. These findings lay the groundwork for further investigations into the immunogenicity and potential applications of these proteins in the diagnosis, treatment, or management of nasal myiasis caused by Oestrus ovis.